Relationship between regional perfusion and oxygenation in patients with coronary artery disease. (22nd September 2015) - Karamitsos, TD; Recio-Mayoral, A; Arnold, JR; Leccisotti, L; Bhamra-Ariza, P; Robson, M; Rimoldi, OE; Camici, PG; Neubauer, S; Selvanayagam, JB
Abstract : Introduction: Elevated deoxyhaemoglobin seen downstream in a territory subtended by a stenotic coronary artery can be assessed by blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI). Previous animal studies have used a T2-prepared steady-state free-precession sequence to determine the BOLD signal in the myocardium. In theory, implementation of this sequence at the higher field strength of 3 Tesla (T) with the expected increase in signal-to-noise and contrast-to noise ratios, would further improve the detection of BOLD signal intensity (SI) changes. We sought to apply this method at 3T in patients with documented coronary artery disease and study the relationship between perfusion measurements by positron emission tomography (PET) and the BOLD signal. Methods: Twenty-two patients (aged 62 ± 8 years, 16 men) with coronary artery disease (at least one stenosis >50% on quantitative coronary angiography) and 10 normal volunteers (aged 52 ± 7 years, seven men) underwent 3T BOLD MRI and PET. For BOLD MRI a midventricular slice was acquired every 30 s at rest and during adenosine stress (140 μg/kg per minute). A set of six images was acquired at rest and at peak stress. Using PET with oxygen 15-labelled water, myocardial blood flow (MBF) was measured at baseline and during adenosine hyperaemia. The BOLD short-axis view was divided into six segments, according to the midventricular segments of the 17-AHA segment model, and mean SI were calculated using QMass (Medis) software. PET images were analysed with MATLAB software (MathWorks Inc) and registered with the BOLD short-axis image using anatomical landmarks. Results: Based on the coronary anatomy, 59 myocardial segments were supplied by significantly stenosed vessels (stenosed segments) and 73 segments were supplied by vessels with minimal or no disease (remote to ischaemia segments). A third group of myocardial segments (n = 60) from normal volunteers was labelled as "normal" segments. Rest MBF (corrected for rate pressure product), stress MBF and BOLD SI change of stenosed, remote to ischaemia and normal segments are shown in the table. Taking quantitative coronary angiography as the gold standard, cut-off values for stress MBF (⩽2.45 ml/min per gram; area under the curve (AUC) 0.83) and BOLD SI change (⩽3.74%, AUC 0.78) were determined to define ischaemic segments. BOLD MRI and PET agreed on the presence or absence of ischaemia in 18 of the 22 patients (82%), and in all normal subjects. With regard to per-segment analysis, taking PET as the gold standard and by applying the cut-off values for stress MBF and BOLD SI, BOLD MRI had moderate sensitivity (63%) but very good specificity (88%) for the identification of ischaemia. The fig shows an example of a patient with significant disease in the right coronary artery. Conclusions: T2-prepared steady-state free-precession 3T BOLD imaging is feasible in the clinical setting and shows good agreement with PET perfusion measurements for the detection of myocardial ischaemia.